X-men milestones: x-tinction agenda ebook - Claremont, Chris (X-Men Milestones., 2019)
Collects Uncanny X-Men (1981) #235-238 and #270-272, New Mutants (1983) #95-97, and X-Factor (1986) #60-62. The biggest and best adventures of Marvel's mighty mutants — these are the X-Men Milestones! The X-Men, New Mutants and X-Factor are targeted for X-Tinction! To rescue a friend, the X-Men must invade the mutant-enslaving island nation of Genosha — but the Genoshans' memories are long, and their revenge will be terrifying! As the Magistrates strike, X-Factor and the New Mutants are drawn into the conflict — and they soon discover old foe Cameron Hodge powered up and pulling the strings! The three X-teams are kidnapped, brainwashed, stripped of their powers and forced into combat — and at least one among them will die! Can the powerless X-Men triumph over the military might of an entire nation? And when the dust settles on this classic crossover, will the X-universe be changed forever?